2021
DOI: 10.1038/s41598-021-98674-6
|View full text |Cite
|
Sign up to set email alerts
|

Systems biology analysis of lung fibrosis-related genes in the bleomycin mouse model

Abstract: Tissue fibrosis is a major driver of pathology in aging and is involved in numerous age-related diseases. The lungs are particularly susceptible to fibrotic pathology which is currently difficult to treat. The mouse bleomycin-induced fibrosis model was developed to investigate lung fibrosis and widely used over the years. However, a systematic analysis of the accumulated results has not been performed. We undertook a comprehensive data mining and subsequent manual curation, resulting in a collection of 213 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Notably, KL (Klotho) gene, which is a pro-longevity gene, was found to be overexpressed in healthy control lung tissues in our study. Consistently, (Toren et al, 2021) also demonstrated that KL is a pro-longevity and anti-fibrotic gene. However, other genes screened in our bioinformatic analysis were not mentioned in the study by Toren et al This discrepancy could be due to the differences in the study design and aims of the two studies.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Notably, KL (Klotho) gene, which is a pro-longevity gene, was found to be overexpressed in healthy control lung tissues in our study. Consistently, (Toren et al, 2021) also demonstrated that KL is a pro-longevity and anti-fibrotic gene. However, other genes screened in our bioinformatic analysis were not mentioned in the study by Toren et al This discrepancy could be due to the differences in the study design and aims of the two studies.…”
Section: Discussionmentioning
confidence: 60%
“…These results support the findings of our bioinformatic analysis and suggest that IGFBP2 may be a promising biomarker of IPF. Moreover, Toren et al (2021) investigated the relationship between lung fibrosis-related and longevity-associated genes in a mouse model of bleomycin-induced fibrosis; they highlighted age as an important risk factor for pulmonary fibrosis and found that pro-longevity genes tended to be related to anti-fibrosis. Our results are partially consistent with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Toren et al found that longevity gene can resist IPF gene through animal experiments, and con rmed that age is an important risk factor for IPF [55].…”
Section: Discussionmentioning
confidence: 99%
“…The mouse bleomycin-induced fibrosis model is generally viewed as the standard in modeling pulmonary fibrosis (Jenkins et al, 2017). Recent studies revealed that genes related to the mouse bleomycin-induced fibrosis model and human IPF have much in common (Bauer et al, 2015;Toren et al, 2021). Interleukin (IL)-13 is a type 2 cytokine with important roles in inflammatory and fibrotic diseases (Gieseck et al, 2018;Bieber, 2020).…”
Section: Discussionmentioning
confidence: 99%